Hemispheric regionalism: border discourse and the boundaries of American studies - Bailey, Caleb (2017)
This thesis engages with and intervenes in a number of insurgent, emergent, and re-emergent, pedagogies and theoretical frameworks of increasing relevance to area studies and, more broadly, challenges the discipline of American Studies to expand its theoretical and textual bases. Here the challenges of transnationalism (as a concern which all area studies need to address) and hemispherism (a concern more specifically related to American Studies) are the key motivating factors for the proposed reconfiguration of the discipline outlined in the thesis. These are pervasive and important strands of political, economic, social, cultural, and academic life, but which the discipline of American Studies has been slow to recognise and incorporate in any meaningful way. The problem here lies in the fact that for American Studies the nation remains an unquestioned and seemingly immoveable priority: studies of the U.S. become as exceptionalist as the object of their study. This project proposes that this subservience to the centre (the nation-state) at the expense of the periphery (the nation’s borders) can be redressed by returning to a much narrower sphere of experience: the region. Paradoxically, this will allow for an expansion of the purview of American Studies, enabling centrifugal readings of American (in its continental sense) culture to develop, rather than the centripetal analyses which have been the subject of much vexed discussion amongst scholars over recent years. By focusing on borders – regions which are always already transnational – this thesis aims to demonstrate that in shifting our focus only slightly beyond national boundaries, new critical techniques might be developed which can revitalise American Studies.